2021
DOI: 10.2196/23200
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Blended Relapse Prevention Program for Anxiety and Depression in General Practice: Qualitative Study

Abstract: Background Existing studies have yet to investigate the perspectives of patients and professionals concerning relapse prevention programs for patients with remitted anxiety or depressive disorders in primary care. User opinions should be considered when optimizing the use and implementation of interventions. Objective This study aimed to evaluate the GET READY relapse prevention programs for patients with remitted anxiety or depressive disorders in gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Potentially, patients with fewer symptoms may not need to engage with the entire program to feel well again and cease using the program after obtaining the benefits [ 35 , 36 ]. At the same time, a qualitative study on the GET READY program indicated that increased symptom levels might also limit patients from further using the program [ 37 ]. An increase in depressive or anxiety symptoms may result in avoidance behavior, which may also lead to avoiding actively working on the web-based modules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potentially, patients with fewer symptoms may not need to engage with the entire program to feel well again and cease using the program after obtaining the benefits [ 35 , 36 ]. At the same time, a qualitative study on the GET READY program indicated that increased symptom levels might also limit patients from further using the program [ 37 ]. An increase in depressive or anxiety symptoms may result in avoidance behavior, which may also lead to avoiding actively working on the web-based modules.…”
Section: Discussionmentioning
confidence: 99%
“…This underlines the importance of the proactive role to be played by MHPs in terms of stimulating patients who are vulnerable to relapsing to continue using the program. Another important way of keeping patients engaged might be the further personalization of the intervention content, for example, by increasing the depth of tailored feedback, providing real-time feedback, and customizing the content based on current symptoms [ 9 , 37 ].…”
Section: Discussionmentioning
confidence: 99%